Inhibition of soluble epoxide hydrolase reverses bone loss in periodontitis by upregulating EMCN and inhibiting osteoclasts - Juanjuan Li; Ni Kou; Xiaoli Shi; Lingwenyao Kong; Weixian Chen; Xueping Yang; Yanrong Zhao; Jie Zhao; Fu Wang (Stem Cell Research & Therapy)
Abstract Background Improving the microenvironment to augment endogenous regenerative potential has emerged as a fundamental concept for stimulating and expediting periodontal tissue repair and regeneration. Previous studies have demonstrated that TPPU, a soluble epoxide hydrolase inhibitor (sEHi), mediates the suppression of inflammatory bone loss in periodontitis models. However, the underlying mechanisms remain largely elusive. Methods In this study, we constructed a human umbilical vein endothelial cell (HUVEC) and periodontal ligament stem cell (PDLSC) coculture system in vitro and tested the anti-inflammatory effect of TPPU under inflammatory conditions. The roles of HIF-1α and Endomucin (EMCN) in the anti-inflammatory effects of TPPU were analyzed. The effects of TPPU on osteogenesis and osteoclastogenesis in cocultured cells were examined. The in vivo periodontitis model further verified the effects of TPPU on inhibiting neutrophil adhesion and inflammation and inhibiting osteoclasts. Results Our in vitro experiments demonstrated that TPPU enhances the interaction between mesenchymal stem cells and vascular endothelial cells to enhance anti-inflammatory and osteogenic differentiation effects and revealed a new anti-inflammatory mechanism of TPPU involving the upregulation of EMCN in endothelial cells to prevent lymphocyte recruitment. We also confirmed that TPPU inhibits osteoclast activity. Our in vivo findings showed that TPPU inhibits osteoclast activity and neutrophil adhesion and enhances periodontal tissue repair and regeneration. Conclusions TPPU promotes local regeneration in periodontitis by inhibiting inflammation and bone resorption. Thus, targeting soluble epoxide hydrolase represents an endogenous regenerative strategy for periodontitis treatment.